Harmful Unbundling - Gabison, Garry A. (Journal of Law and Commerce, 2021)
Companies have been unbundling their product: they have been selling separately products and services that were traditionally sold together. In doing so, they have raised their profits. This paper uses a model to show how companies can use unbundling to increase profits and decrease competition. Unbundling raises problems when it increases information cost, information asymmetry, and barriers to entry. This paper also discusses the US case laws that have grasped with these issues of bundling and unbundling.